Eficacia de la aplicación del hipoclorito de sodio al 5 porciento, para mejorar el blanqueamiento dental con la técnica de consultorio - Medina Suárez, Alex Santiago (2017)
Introduction: The objective of the investigation is to evaluate the results of a dental clearance therapy with a modification in the conventional technique, evaluating the time of exposure and final result of the clearance. Method: Using 5 percent sodium hypochlorite as an enamel conditioner prior to the application of 35 percent hydrogen peroxide in a hemiarcate per patient and a single clearing session. Using the of conventional color evaluation and also a method of objective evaluation as the spectrophotometer records the colors obtained in the Vita 3D Master Bleach scale, Vita 3D Master, Vita classic, CIElab; Previous and after therapy bleaching to compare. It also includes assessment of sensitivity by means of a VAS scale that produced the value statistically comparable. Conclusions: The treatment of dental clearance with the two consulting techniques was effective and obtained similar results, so there was no significant change to using 5 percent sodium hypochlorite as an enamel conditioner.